Spatial Distribution of Poverty in Chile - Agostini, Claudio (Estudios de Economía, 2016)
Chile’s recent success in reducing poverty has been remarkable, with povertyrates falling by approximately two-thirds over the last 20 years. However, furthergains against poverty may be inhibited by the increasing difficulty associatedwith targeting fewer poor people and better, more localized information may thusbe required. Moreover, public policy that seeks to understand the relationshipbetween poverty, socioeconomic status and urban or rural residence depends onsurvey data that may not be representative at low levels of aggregation; althoughcensuses are representative by definition, they generally lack detailed income data.Recent mapping techniques combining census and survey data afford detaileddescriptions of the spatial distribution of poverty. Indeed, such techniques enablethe calculation of robust and statistically precise estimates of poverty at low levelsof aggregation, allowing a more nuanced picture of poverty to emerge. In thispaper we use such methodologies to produce consistent estimates of both rural andurban poverty at the county level in Chile. The results demonstrate considerableheterogeneity in local poverty, suggesting that future antipoverty policies mustbe targeted at the local level. Moreover, the estimates we provide may be usedto further analyze the causes and consequences of localized poverty.